2022
DOI: 10.1039/d2an00020b
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidics-based rapid measurement of nitrite in human blood plasma

Abstract: Nitric oxide (NO) is one of the vital gasotransmitters that takes part in many biological pathways such as infection, inflammation and ischemia, immune response, neurotransmission, and cardiovascular systems. Nitrite is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Principally, our sensor showed impressive LoD and sensitivity. From previous studies, the nitrite concentration in healthy human blood is in the range of 0.4–1.2 µM [ 60 ]. The wide linear range of this nitrite sensor can be useful to analyze nitrite levels in real samples directly, without diluting samples.…”
Section: Resultsmentioning
confidence: 99%
“…Principally, our sensor showed impressive LoD and sensitivity. From previous studies, the nitrite concentration in healthy human blood is in the range of 0.4–1.2 µM [ 60 ]. The wide linear range of this nitrite sensor can be useful to analyze nitrite levels in real samples directly, without diluting samples.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, identification of a method characterized by instant monitoring, low cost, and easy operation has become a research hotspot. Paper-based analytical devices (PADs) may provide point-of-care diagnostics with a potential solution [68][69][70][71][72][73][74][75][76][77][78][79], as summarized in Table 5. The schematic assembly of the PAD reported by Noiphung et al [70] is shown in Figure 11.…”
Section: Paper-based Analytical Devicesmentioning
confidence: 99%
“…Gaikwad et al [78] reported a fluorescence-based microfluidic method to improve the sensitivity of µPADs. In the range of 0 µM−20 µM, there was good linearity, and sensitivity was greatly improved (LOD: 60 nM).…”
Section: Paper-based Analytical Devicesmentioning
confidence: 99%